Effectiveness and safety of the recombinant zoster vaccine in adult patients with systemic lupus erythematosus: a claims-based retrospective cohort study in the USA - Alexis Ogdie; Michael D George; Huifeng Yun; Kristin Palmsten; Omar Ali; Cheryl N McMahill-Walraven; Aziza Jamal-Allial; Mano Selvan; Djeneba Audrey Djibo; Driss Oraichi; Sophie E Mayer; Sheryl A Kluberg; et al. (RMD Open)
Objectives To assess vaccine effectiveness (VE) and safety of the recombinant zoster vaccine (RZV) in adults with systemic lupus erythematosus (SLE).Methods This retrospective study using administrative claims data collected between 1 January 2018 and 30 September 2023 from the USA included two cohorts of adults aged ≥18 years with SLE insured by (1) Medicare (parts A/B/D) or (2) one of five commercial partners (including Medicare Advantage plans). In VE analyses, adults receiving two RZV doses ≥28 days apart were matched 1:4 to unvaccinated comparators on insurer, sex and age (±5 years); the outcome was incident herpes zoster (HZ) after 31 days. In safety analyses, adults receiving RZV dose 1 or 2 were matched to unvaccinated comparators as above; the outcome was severe SLE flare within 90 days. Adjusted hazard ratios (HRs) were estimated using Cox models with inverse probability of treatment weighting (IPTW).Results VE cohorts included 2284 Medicare and 1308 commercially insured RZV-vaccinated patients; mean weighted follow-up was 1.4–1.6 person-years. Safety cohorts included 6602 RZV vaccinations (dose 1 or 2) in Medicare and 4196 in commercial insurers. Vaccinated versus unvaccinated patient characteristics were balanced after IPTW. VE was 70% (95% CI: 50% to 82%) in Medicare and 54% (95% CI: 18% to 74%) in commercially insured patients. The HR of severe SLE flare in vaccinated versus unvaccinated patients was 0.91 (95% CI: 0.75 to 1.11) in Medicare and 0.94 (95% CI: 0.72 to 1.24) in commercially insured patients.Conclusions RZV prevented a majority of HZ cases in individuals with SLE without increasing the risk of severe SLE flare.